Uitgangspunten voor Keteninformatisering - Visser, Tjitske (Igitur, 2013)
This article is only available in Dutch. Chain-computerisation is gaining increasing attention but many large-scale IT projects do not always lead to the expected success. Based on insights from the doctrine Chain Computerisation this article gives a number of characteristics and principles for chain computerization to be able to increase the likelihood of success of these projects.
Keywords: Informatica; Rechtsgeleerdheid; Economie; Bestuurs- en organisatiewetenschap; chain-computerisation; interorganisational cooperation; principles